Role of Social Workers in Enhancing Chronic Care: A Case Study of Kabale Regional Referral Hospital Kabale District. - Musiimenta, Moureen (Kabale University, 2024)
This study examines the essential role of social workers in improving chronic care, with a focus on Kabale Regional Referral Hospital in Kabale District, Uganda. Chronic diseases present a major global healthcare challenge, necessitating integrated and holistic care approaches that go beyond medical treatment. In this context, social workers play a critical role by addressing patients' psychosocial, economic, and emotional needs. The study utilized a descriptive research design and engaged a sample size of 45 respondents. Both qualitative and quantitative methods were employed for data collection and analysis. To ensure an equal chance for participation, simple random sampling techniques were applied, while purposive sampling was used to target specific respondents who contributed valuable insights to the study. The findings, analyzed according to the study’s specific objectives, are summarized in chapter five. Recommendations include addressing challenges in social work and social administration through enhanced social work education and professional practice, emphasizing the combined role of academic knowledge and fieldwork in fostering community development. The study advocates for the need for well-trained, practice-oriented, and committed social workers who can improve the socio-economic status and quality of life of community members. The study concluded that social work and social administration is a dynamic profession with broad applications. The primary methods of social work, which include participatory approaches with individuals, groups, and communities, are complemented by secondary methods that combine participatory and non-participatory strategies for societal benefit. Social workers fulfill diverse roles that evolve across different contexts and stages of their careers. These roles, as documented in the study, highlight the expansive impact of social workers in enhancing individual, group, and community welfare.